Effect of Reading Workshop Learning Model on Reading Comprehension Skills and Reading Motivation of Fourth Grade Elementary School Students - Evie Nurfawati; Tarman A. Arief; Haslinda Haslinda (Universitas Pendidikan Indonesia (UPI), 2023)
This research is motivated by the low reading comprehension skills and reading motivation of students in learning Indonesian reading comprehension skills in elementary school. The purpose of this study was to determine the effect of the Reading Workshop Learning Model on reading comprehension skills and reading motivation of fourth grade students of SDIT Al-Fityan School Gowa, Gowa Regency. The method used in this study is a quasi-experimental method with a nonequivalent control group design. The population in this study were all 4th grade students of SDIT Al-Fityan School Gowa, totaling 112 students. Purposive sampling is used to determine the sample to be studied with sampling criteria based on certain considerations. The sample selected was class IV.C as the control class with 28 students and class IV. D as the experimental class with 28 students. Data collection techniques through test instruments and questionnaires. Data analysis of test results to determine students' motivation and reading comprehension skills were analyzed using descriptive analysis and inferential analysis, through independent sample T-test and Manova test which showed that students' reading comprehension skills got an average pretest score of 76.11 and an average pretest score of 76.11. average posttest 89.54. The results of the independent sample T-test are Tcount = 5.562 Ttable 1.674 and the value of sig. ie 0.000 0.05. The results of students' reading motivation obtained a value of Tcount 5.648 Ttable 1.674, the value of sig. 0.000 0.05. Manova test results = 0.000 0.05, which means Ha is accepted and Ho is rejected,